Capital account liberalisation on economic growth: a perspective from emerging economies - Koh, Kai Vern (2018)
Literature findings on the relationship between capital account liberalization and economic growth appear mixed. This phenomenon is even more prominent in the case of emerging markets. Investigations were thereby carried out to determine the effects of capital account liberalisation, and if such effects vary based on the type of the economy. Additionally, a corollary hypothesis considers differing impacts on capital account openness given the presence of other variables. De jure measures of capital account openness were used as part of the research, concerning data for 47 emerging and advanced countries from 1960 onwards. Potential interactive impacts of the capital account openness indicator were included to extend findings on the possible association and dependency with other variables. Quadratic effects were employed in this literature to address possible differing effects of capital account openness between emerging and advanced economies. OLS, GMM-SYS estimators and pooled time series were used to study for possible growth regressors and its effect on economic growth rates. Our findings show a positive association between capital account liberalisation with subsequent growth in both emerging and advanced economies. Such effects of the capital account openness index remain robust even after we consider for other variables such as black-market premium, corruption and regulatory quality. Compared to advanced economies, emerging countries were found to gain higher economic growth with capital account openness.